Diagnostic Value of Breast Proton Magnetic Resonance Spectroscopy at 1.5T in Different Histopathological Types - Hyeon-Man Baek (The Scientific World Journal)
The purpose of this study was to investigate the usefulness of quantitative proton magnetic resonance spectroscopy (1H-MRS) for characterizing breast lesions at 1.5T, and to evaluate the diagnostic performance of in vivo breast 1H-MRS using receiver operating characteristics (ROC) analysis. 112 patients (99 malignant and 13 benign tumors) who were scanned with the MRI/MRS protocol were included in this study. Choline-containing compounds (tCho) levels were measured and compared with histological findings. The measured tCho levels in this work had range of 0.08–9.99 mmol/kg from 65 (66%) of 99 patients with malignant tumors. Of the 13 benign lesions, 1H-MRS detected one as false positive, with tCho level of 0.66 mmol/kg. The optimal tCho level cutoff point that yielded the highest accuracy was found to be >0.0 mmol/kg. The resulting sensitivity was 66% and specificity 92% for distinguishing benign from malignant lesions. The tCho levels were found to be higher in invasive cancer compared to ductal carcinoma in situ or benign lesions, possibly associated with more aggressive behavior or faster cell replication in invasive cancer. Quantitative in vivo  1H-MRS may provide useful information for characterizing histopatholoigical types in breast cancer.